2016
DOI: 10.1002/chem.201603303
|View full text |Cite
|
Sign up to set email alerts
|

Radical Reactions Induced by Visible Light in Dichloromethane Solutions of Hünig's Base: Synthetic Applications and Mechanistic Observations

Abstract: β-(3-Iodopropoxy)-substituted α,β-unsaturated lactams, lactones, and cycloalkenones (eight examples) underwent reductive radical reactions in a dichloromethane solution of N,N-diisopropylethylamine (Hünig's base) upon irradiation with visible light (λ=419 nm). Apart from plain reduction reactions (hydro-de-iodination), a significant degree of cyclization was observed in three cases. In parallel to the conversion of the substrates, the formation of intensely colored by-products was observed. Based on mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…The formation of chlorostreptocyanine 10 is consistent with a recent publication from the Bach group, in which similar but non‐chlorinated cyanines were detected as the products of the reaction of CH 2 Cl 2 and DIPEA (diisopropylethylamine). These conjugated chromophores resulting from N ‐dealkylation/condensation with the polyhalomethane, and reaction of the resulting iminium salts with enamines (formed through oxidation/deprotonation) were shown to be responsible for the amber color in similar photoinduced reactions …”
Section: Resultsmentioning
confidence: 99%
“…The formation of chlorostreptocyanine 10 is consistent with a recent publication from the Bach group, in which similar but non‐chlorinated cyanines were detected as the products of the reaction of CH 2 Cl 2 and DIPEA (diisopropylethylamine). These conjugated chromophores resulting from N ‐dealkylation/condensation with the polyhalomethane, and reaction of the resulting iminium salts with enamines (formed through oxidation/deprotonation) were shown to be responsible for the amber color in similar photoinduced reactions …”
Section: Resultsmentioning
confidence: 99%
“…purified Et 3 N) are competent base catalysts (Table 1, entry 2). Third, when running the reaction in CD 2 Cl 2 (which can transfer •D) 17 D was, not incorporated into the product. Fourth, reactions run in presence of radical traps (e.g.…”
mentioning
confidence: 99%
“…Second, although the reaction utilizes TMG (which can have inorganic impurities that can oxidize a thiolate), other amine bases that lack such impurities (e.g., purified Et 3 N) are competent base catalysts (Table , entry 2). Third, when running the reaction in CD 2 Cl 2 (which can transfer ·D) D was not incorporated into the product. Fourth, reactions run in the presence of radical traps (e.g., 1,4-dicyanobenzene and BHT) proceed to full conversion and comparable yields.…”
mentioning
confidence: 99%
“…The inclusion of water may either prevent their formation or hydrolyze them if they do form. 52,53 We had presumed that the amine indirectly (as the radical cation) served as both the terminal reductant and the source of a H atom in the formation of the diene. However, we found that when normal water was replaced with heavy water (15 equiv D 2 O, Scheme 3a) the reaction resulted in 69% deuterium incorporation into the diastereotopic methylene signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%